Long‐term Follow‐up of Cervical Facet Medial Branch Radiofrequency Treatment With the Single Posterior‐lateral Approach: An Exploratory Study. Issue 1 (18th March 2013) - van, Maarten; de, Nelleke; Dortangs, Erik; Kessels, Alfons; van, Jan; Lataster, Arno; Patijn, Jacob; van, Maarten
Abstract Background Over 50% of patients presenting to pain clinic with neck pain have the cervical facet joints as the source of pain. Radiofrequency (RF) treatment of the medial branch, innervating the facet joint, is a therapeutic option. The objectives of this study were to evaluate the therapeutic effect and its duration of RF treatment, using the single posterior‐lateral approach in patients suffering from facet joint degeneration and to identify predictors for a long‐term effect. Methods Of the 130 consecutive patients with axial neck pain referred to the University Pain Center Maastricht, 67 fulfilled the inclusion criteria. The therapeutic effect was measured using the Patients' Global Impression of Change (PGIC) scale. Retrospective data were made complete using newly collected PGIC follow‐up data. A Kaplan–Meier curve evaluated the long‐term therapeutic effect. Possible predictors of outcome were evaluated. Results Two patients refused to participate and in the remaining 65 patients, overall pain relief was reported in 55.4% at 2‐month follow‐up. Moderately, important change of improvement and substantial change of improvement were seen in 50.8% of patients. At 3‐year follow‐up, 30% still reported pain reduction. Spinal treatment level was the only predictor found. Conclusions Radiofrequency treatment of the cervical facet joints using a single posterior‐lateral approach is a promising technique in patients with chronic neck pain due to facet degeneration. The short‐term and long‐term therapeutic effects of this intervention justify a randomized controlled trial to estimate the efficacy of cervical facet joint RF treatment in a chronic neck pain population.